CONTROL METHODS OF OCCUPATIONAL HAZARDS IN REPAIR FACILITIES OF ENGINEERING INDUSTRY - Mohammed Neamah Mohsen; Maria Alexeyevna Zhuravleva (Advanced Engineering Research)
Measuring methods of the gas concentration in the working area air of the mechanical-engineering repair facilities are considered. The gas-sensitive sensor types are compared. A classification of the occupational hazards is presented; their health effect is described. The object of this study is a standard repair facility of the mechanical-engineering industry. The workplace assessment charts of one of the electric locomotive repair works are analyzed. Some issues on the acceptable working conditions ensuring, and on decreasing their harmful level are considered. To solve the task of monitoring the occupational hazards, the application of the wireless sensor networks (WSNs) is proposed. The sensor types best suited for the application in the WSN are described. The results of the research conducted allowed making the conclusions on the feasibility of the wireless sensor networks in the safety management systems in the mechanical-engineering repair facilities.